Queering the South on screen - Pugh, Tison, 1970- (The University of Georgia Press, 2020)
"Within the realm of U.S. culture and its construction of its citizenry, geography, and ideology, who are Southerners and who are queers, and what is the South and what is queerness? Queering the South on Screen addresses these questions by examining "the intersections of queerness, regionalism, and identity" depicted in film, television, and other visual media about the South during the twentieth century. From portrayals of slavery to gothic horror films, the contributors show that queer southerners have always expressed desires for distinctiveness in the making and consumption of visual media. Read together, the introduction and twelve chapters deconstruct premeditated labels of identity such as queer and southern. In doing so, they expose the reflexive nature of these labels to construct fantasies based on southerner's self-identification based on what they were not"- Resumé vydavatele
Keywords: film -- 20.-21. století -- Spojené státy americké (jižní oblast); televize -- Spojené státy americké (jižní oblast) -- 20.-21. století; gender; identita; film -- 20th-21st century -- United States, Southern; television -- 20th-21st century -- United States, Southern; identity; monografie; monographs